Gaston Bachelard: i sogni dell’immaginazione materiale e il cosmo di ferro (Altre Modernità, 2012)
Gaston Bachelard’s incursions into the beaten tracks of image creation inaugurate a new conception of imagination. By departing from a criticism of what is called reproductive imagination, which is based on the contemplation of things, he shows instead that true imagination is creative because it instantiates a surreal world. The purpose of this work is to understand the process of image production, as well as the creative act inherent to imagination. In order to accomplish this, we revisit the notion of ‘material imagination’, which we consider an essential pressuposition in the more poetic side of Bachelard. Even though it is well known that Bachelard privileges poetry and literature over other art forms, we turn our attention to the philosophical texts in which he talks about the plastic arts, such as painting and sculpture, in order to demonstrate the salutary action of the dreams of the will on the subject, as well as the importance of the manual work of the artist which has been made dynamic by his creative work. Our study will take the analysis of the work of Eduardo Chillida made by Bachelard, in order to show in what sense a sculptor, who becomes a metalworker, succeeds at plunging into the dreams of iron and, by perceiving the metal propagating its force, creates artistic works which present themselves as materialized echoes of the beating of the hammer on iron. It will become obvious in the conclusion of this essay that true imagination cannot simply be a copy of reality. By distancing itself from sensible reality, the artist’s imagination succeeds in constructing images that are fundamentally material ones. On their turn, these make possible for the artist to surpass, by means of a struggle between his hands and the matter of the world, the level of everyday life, thus reaching out to what can be taken as a true aesthetic revolution.